A Pre-Experimental Research on the Implementation of Selected Classroom Assessment Techniques for Music, Arts, Physical Education, and Health - Tabuena, Almighty (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The primary objective of this study is to examine and identify the classroom assessment techniques (CATs) that might provide and help teachers through assessment and evaluation processes in Music, Arts, Physical Education, and Health (MAPEH) using pre-experimental research through one-group pretest-posttest design. The study was conducted at Jose Abad Santos High School in Manila, Philippines during the third grading period of the researcher’s practicum. The sample of the study consists of 20 students selected through the purposive sampling technique. Quantitative and qualitative data analyses were employed. The instruments used in the study were a teacher-made quiz, CATs sample assessment as the treatment, and the perception survey questionnaire (PSQ) regarding the CATs. The result revealed that there is a significant difference between the pre-evaluation and post-evaluation after the CATs implementation. In the post-evaluation, the mean score was significantly higher than the pre-evaluation, which indicates that the CATs improved the performance of students in MAPEH. On the other hand, as revealed in the PSQ, the students regarded the CATs positively. It shows, in this case, that CATs are a great alternative to traditional assessments. Other CATs to be developed and implemented for better learning and effective teaching are recommended.